Social media portfolio report / Nur Hasyimah Abdul Khalil, Siti Hajar Ismail and Wan Syamin Izzati Wan Suhaimi - Abdul Khalil, Nur Hasyimah; Ismail, Siti Hajar; Wan Suhaimi, Wan Syamin Izzati (2017)
Seek.My is a start-up vintage and prelove online store and thrift shop establishment located in the heart of Kuala Lumpur. Seek.My is a vintage and prelove online platform for vintage lovers managed by three young female entrepreneurs, Nur Hasyimah Binti Abdul Khalil (31), Siti Hajar Binti Ismail (22), and Wan Syamin Izzati Binti Wan Suhaimi (22). Venturing into business with a small team of trusted and like-minded individuals, these partners represent sales, operation management, and finance and administration areas, respectively. The partners provided funding from their own savings, which will cover start-up expenses and provide a financial cushion for the first months of operation. Seek.My aims to offer its vintage collection and prelove products at a competitive price to meet the demand of the middle to higher income local market area residents and tourists. Seek.My expects to catch the interest of a regular loyal customer base with its variety of vintage collections and prelove stuffs. The company plans to build a strong market position in Kuala Lumpur, due to the partners' industry experience and mild competitive climate in the area.